Optimization of surgical methods for the treatment of gynecomastia - A.G. Ihnatieva; S.M. Yurchyshyn (Медицина неотложных состояний)
Background. Gynecomastia has a negative impact on the psychological state of men. Optimisation of surgical treatment for gynecomastia, aimed at minimising unsatisfactory cosmetic consequences of operation, should significantly improve the quality of life of patients. The purpose of the study: to improve the surgical technique of treatment for gynecomastia by optimising the area of transdermal intervention with an emphasis on minimising postoperative complications and scars. Materials and methods. A total of 132 patients (mean age 31.5 ± 2.8 years, body mass index 25.2 ± 3.4, I–II ASA) were operated for gynecomastia. Gynecomastectomy (GME) was performed in patients who were randomly divided into two groups: control (C) and main (M). Patients in group C (n = 80) underwent standard GME with 10–15-mm crescentic incisions along the nipple. Patients of group M (n = 52) were operated with vertical incisions on the nipple-areolar complex at the conditional 12th and 6th hours with a length of 5–7 mm. Statistical analysis of the study results was performed according to the criteria of Pearson, Fisher and Kruskal-Wallis (Stata 12.1 package). After 3 months, the patients were questioned. The following method was used to assess surgical outcomes: 1 point — dissatisfied, 2 points — relatively satisfied, 3 points — satisfied. Results. Patients in group M had significantly fewer complications and a shorter hospital stay by 2 days (p < 0.001). 94.2 % of patients in group M at follow-up survey reported satisfaction with the results of GME in contrast to group C, where 38 % of respondents expressed dissatisfaction with the consequences of GME. The vertical incision technique showed a better cosmetic effect — a significant decrease by 13.4 times (p < 0.001) in the scar area (174.0 ± 12.0 mm2 vs. 13.0 ± 2.0 mm2). Conclusions. The use of the proposed GME demonstrated better cosmetic efficacy, namely a 13.4-fold (p < 0.001) reduction in scar area to 13.0 ± 2.0 mm2 compared with the standard GME (174.0 ± 12.0 mm2). In addition, GME patients with vertical incisions had a reduction in the length of hospital stay by 2 days (p < 0.001). The method of optimised GME demonstrated a 1.8-fold higher level of patient satisfaction with the results of the operation according to a survey conducted 3 months after GME. The use of compression garments after surgery was mandatory, which contributed to better recovery.